SEDIMEN DAN MANFAATNYA - Helfinalis Helfinalis (OSEANA, 2018)
SEDIMENT AND ITS BENEFITS. Sediment deposition is a form of compact material that accumulates on the surface or near the surface of the earth, under conditions of low pressure and temperature. Sediment is generally a product of old rock destruction which is transported and distributed by water or wind currents. Sediments are the result of chemical or biochemical precipitation of the solution. Learning the distribution of sediment on the seabed is desperately needed and very useful, for the initial phase to lay the wire and pipe lines on the sea, consider topography of sea (bathimetry), sedimentary texture and ocean currents. Clays are considered unfavorable for the laying of construction pole as a result of clay having a high volume change potential. Clay will undergo expansion when water increases and shrinkage occurs when the water content is less. Rock sediments of sand and limestone are useful for building materials.